PREVALENCE OF COLOR BLINDNESS IN ELEMENTARY SCHOOL-AGE CHILDREN PATIENTS AT KUTIME HEALTH CENTER, TOLIKARA DISTRICT, PAPUA PEGUNUNGAN: Oral Presentation - Observational Study - General practitioner - Ferdiansyah, Muhammad; Lovita, Audra; Daeli, Rahmat P. (Ophthalmologica Indonesiana, 2024)
Introduction & Objectives Color blindness is a genetic disorder in the form of an inability or decreased ability to see color differences. Incidents of ignorance are widely reported in aspects of everyday life, such as in the learning process, further education, and career determination. Causing disappointment in children’s aspirations because it was not detected early. Methods This research is descriptive with cross-sectional design and total sampling technique. The sample for this study were all pediatric patients aged 6-12 years who went to the Kutime Health Center who were familiar with numbers and were carried out from June to December 2022. The method used a pseudoisochromatic plate (Ishihara). Results There were 105 children who participated in the study, while only 55 children met the inclusion criteria. Of these, there were 32 boys (58.1%) and 23 girls (41.8%). The number of cases of color blindness in children who went to the Kutime Health Center was 1 child (1.85%). Color blind patients were boys (3.2%), there were no color blind girls in this study (0%). Conclusion The prevalence rate of color blindness in the Kutime Health Center (1.85%) is still above that in Papua Province (1.39%) and nationally (0.7%). Color blindness affects more men than women, especially anyone with family history of color blindness. This research invites early detection so that they understand about the child’s condition, the aspirations children instill can be accommodated earlier so that there will be no disappointment regarding the choice of further education or their future career.